Direct electrical switching of ferroelectric vortices by a sweeping biased tip. (1st October 2018) - Ma, L.L.; Ji, Ye; Chen, W.J.; Liu, J.Y.; Liu, Y.L.; Wang, Biao; Zheng, Yue
Abstract: The precise manipulation of ferroelectric vortices is one of the most important issues concerning its potential applications in functional electronic devices such as non-volatile memory. Despite investigations focusing on the switching of toroidization of vortex domain structure performed in recent years, there is still a lack of a simple and general method to realize vortex switching. In this work, we propose a direct electrical method to switch ferroelectric vortices by sweeping a biased tip, which is easy-to-operate in practice and is demonstrated to be feasible for various ferroelectric structures. It is the electric field gradient generated by the tip bias in conjunction with the time-reversal asymmetric tip-sweeping operation that induces the vortex switching. The influencing factors of this method, e.g., field profile, tip size, tip bias, tip displacement and surface screening conditions, etc., are systematically studied. As an implementation, we put forward a nanowire vortex memory system in which the information stored by vortex chirality can be successfully manipulated by the tip-sweeping method. The effects of temperature and nanowire structure on the feasibility of vortex switching are analyzed. Our findings provide an efficient control strategy on ferroelectric vortices and suggest broad device opportunities exploiting vortex domain structures.